2012
DOI: 10.1021/cm3031363
|View full text |Cite
|
Sign up to set email alerts
|

Relaxor-like Dielectric Behavior in Stoichiometric Sillenite Bi12SiO20

Abstract: A combination of fixed frequency dielectric measurements (103 to 106 Hz) and impedance spectroscopy reveal evidence of (nonferroelectric) relaxor-like behavior in the temperature range ∼600–750 K for the stoichiometric sillenite phase Bi12SiO20 (space group I23, a = 10.1034(5) Å). Variable temperature Raman Spectroscopy reveals significant changes associated with the Bi–O framework vibrations, and the relaxor-type behavior is attributed to noncorrelated local dipole moments associated with the BiO5E (E = 6s2 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…We note that a similar effect has been seen in the stoichiometric sillenite phase, Bi 12 SiO 20 [47].…”
Section: Bi 25 Feo 39supporting
confidence: 78%
“…We note that a similar effect has been seen in the stoichiometric sillenite phase, Bi 12 SiO 20 [47].…”
Section: Bi 25 Feo 39supporting
confidence: 78%
“…19 The BMOs are of great importance because of their interesting photorefractive, photochromic, dielectric properties [20][21][22] and promising industrial applications in the fields of optical signal processing, phase conjugation, image amplification, holographic data storage, real-time holography, and optical communications. 22,23 In recent years, the photocatalytic properties of BMOs have also attracted increasing attention for decomposing organic pollutants. For instance, Yao et al 24 reported that Bi 12 TiO 20 with a band gap of about 2.4 eV and Ba-doped Bi 12 TiO 20 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…It corresponds to the electric conductivity relaxation process, which was determined in the former works. 14,19,21 The epoxy-glue sample shows two orders lower electric permittivity in comparison to BM ceramics ( Figure 5(b)). The addition of BM to the epoxy-glue matrix resulted in e 0 (T) decrease by two orders in respect to the reference BM ( Figure 5(c)).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…This phase shows indirect gap equal to 0.78 eV 20 than the Bi 12 MnO 20 phase, with E gap ¼ 1.66 eV. 10,21 Moreover, BiMn 2 O 5 exhibits antiferromagnetic order below $40 K. 20,22 The non-polar BM ceramics, exhibited high value electric permittivity, " 0 & 10 3 to 10 4 , and dielectric losses coefficient, tan & 1-20, in vicinity of room temperature, dependably of measuring frequency. It has been determined that BM exhibits two relaxation processes, which correspond to activation energy, E A ¼ 0.19 eV and 0.24 eV, respectively.…”
Section: Introductionmentioning
confidence: 97%